(untitled) (Altre Modernità, 2024)
This article presents a teaching activity carried out as part of the TikTok Mundi internship. The paper, which is addressed to an audience that is not specialised in the specific discipline, opens by outlining the linguistic and geographical boundaries of the ‘Arabic world’, emphasizing the need for critical reflection on the related – distinct yet interrelated – concepts of linguistic and cultural domains. It offers sociolinguistic remarks on the pluriglossic reality of the Arabic world, on the variants of Arabic, and on common language devices, such as code-mixing and code-switching. Finally, it considers the use of social media by the young segment of the population of Arab countries and how they use different language varieties, also considering some social implications and the modifications that this context of use may induce in the language itself.